2008
DOI: 10.1016/j.cogpsych.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prototypicality in sentence production

Abstract: Three cued-recall experiments examined the effect of category typicality on the ordering of words in sentence production. Past research has found that typical items tend to be mentioned before atypical items in a phrase-a pattern usually associated with lexical variables (like word frequency), and yet typicality is a conceptual variable. Experiment 1 revealed that an appropriate conceptual framework was necessary to yield the typicality effect. Experiment 2 tested ad-hoc categories that do not have prior repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
0
23
1
Order By: Relevance
“…Our results, therefore, do not allow for interpretations as to the effects of individual conceptual factors or differences between them (as discussed in e.g. Onishi et al, 2008). However, the overall pattern of results, with strong effects of the conceptual variables, gives us confidence that some conceptual properties, and thereby differences in lemma activation, do influence order in NP conjuncts.…”
Section: Overviewcontrasting
confidence: 60%
See 2 more Smart Citations
“…Our results, therefore, do not allow for interpretations as to the effects of individual conceptual factors or differences between them (as discussed in e.g. Onishi et al, 2008). However, the overall pattern of results, with strong effects of the conceptual variables, gives us confidence that some conceptual properties, and thereby differences in lemma activation, do influence order in NP conjuncts.…”
Section: Overviewcontrasting
confidence: 60%
“…In contrast, Kelly et al (1986) and Onishi et al (2008) report influences of the conceptual variable 'category typicality' on order in NP conjuncts. With this variable, however, it is currently unclear whether it should be regarded as an effect of conceptual or lexical accessibility (Onishi et al, 2008).…”
Section: Order In Np Conjuncts In Models Of Language Productionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the functional/positional distinction provided a good account of how animacy or imageability influenced word order in the production of English sentences, other studies have found that message-related factors like referential availability and typicality can influence the order of elements in a conjunction (Bock & Irwin, 1980;Kelly, Bock, & Keil, 1986;Onishi et al, 2008). Furthermore, conceptual factors like animacy and referential availability can influence the order of nouns in a conjunction when it is presented in isolation both in adults and children (Byrne & Davidson, 1985;McDonald et al, 1993;Narasimhan & Dimroth, 2008).…”
Section: Word Ordering Phenomena In English and Japanesementioning
confidence: 94%
“…This preference can even induce speakers to use a less frequent syntactic structure, such as the passive, to obtain early placement of accessible words (McDonald, Bock, & Kelly, 1993; e.g., ''The students were frightened by the sound" was preferred over ''The sound frightened the students"). A wide variety of conceptual and lexical factors related to the accessibility of words have been found to modulate structure selection (e.g., Bock, 1986;Bock, 1987;Bock & Irwin, 1980;Bock & Warren, 1985;Onishi, Murphy, & Bock, 2008;Prat-Sala & Branigan, 2000). However, these conceptual and lexical accessibility phenomena depend on the syntactic context that they occur in.…”
Section: Introductionmentioning
confidence: 96%